Tea pests and pesticide problems and integrated management - Shrestha, Gita; Thapa, Resham B (Journal of Agriculture and Environment, 2015)
Tea is one of the most popular beverage and main cash crops of Nepal with a very high export potential. Its plantation has expanded over 19000 ha with production of nearly 21 million kg per annum providing employment opportunity to 12000 farmers and many traders in Nepal. This plant suffers from more than 300 recognized pests, of which 25-30 insect pests occur regularly in poorly managed tea garden and some of them are major ones causing significant crop loss. Their recognition of field occurrence and incidence helps in devising management options to reduce crop loss. Therefore, a study was conducted to monitor insect pests, ascertain their nature of incidence and time of occurrence in tea garden in terai (Bhadrapur), foot-hill (Barne) and mid- hill (Kanyam) of eastern Nepal. Information was gathered by interacting with local tea gardeners, close observation in the field, collection of species and their identification in the laboratory, which showed that both terai and foot-hills with warmer climate harbored higher number of species than mid-hills. Their integrated management is essential for sustainable tea production.